HUBUNGAN PENGGUNAAN AKSES INTERNET DENGAN SIKAP SEKSUALITAS REMAJA DI PERUMAHAN PURI PERMAI RW 05 TAHUN 2018 - Nuryanti Nuryanti; Kustini Rahayu (Universitas Yatsi Madani, 2018)
This research uses quantitative as the research methodology, the type of the research is correlational and The research design is using Cross Sectional. The sampling technique in this research uses quota sampling technique to determine the sample size of population of certain characteristics until the researcher found the desired sample. The quota sample in this research is 120 adolescent respondents. Based on the research conducted at PuriPermai Residences RW 05 in 2018, bivariate analysis revealed that there is a relationship between adolescents’ use of internet and their sexual attitude with P-value of 0,039. It shows that P-value <α value equal 0,05; thus, it can be concluded that there is a significant relationship between adolescents’ use of internet and their sexual attitude at PuriPermai Residences RW 05. The conclusion is, 59 adolescent respondents (49,2%) are classified as heavy internet users and 34 adolescent respondents (28,3%) are having negative sexual attitude. Adolescents are expected to use internet in a positive way. They are expected to use internet as a tool to increase their religious understanding to prevent negative sexual Attitude